High quality alfalfa in short supply - now what? - Dunham, James R. (Kansas Agricultural Experiment Station, 2011)
Wetter than normal growing and harvesting conditions have resulted in a short supply of high quality alfalfa. Because forage quality affects milk production in early lactation cows, dairy farmers are encouraged to consider other alternatives to feeding low quality alfalfa to high-producing dairy cows.
Keywords: Dairy; Alfalfa quality; Alfalfa prices; By-products; Relative feed value; Forage